Precise two-pin voltage reference - Aung Kyaw Lwin (2008)
Voltage references are essential parts of most electrically powered systems. Though simple references are often sufficiently accurate to meet the demand of most applications, precision references are still needed in many applications. The accuracy of precision voltage references can be improved by attempting to cancel the linear (first-order) and nonlinear (second and high-order) components of base-emitter voltage of a bipolar transistor.